DILEMA PARENTING DI ERA DIGITAL: MENEMUKAN KESEIMBANGAN ANTARA MODERNITAS DAN NILAI-NILAI LOKAL (STUDI KASUS GENERASI Z DAN SUKU BADUY) - Milawati Valantia; Munawaroh Munawaroh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The digital era presents significant challenges to traditional parenting, particularly in maintaining a balance between modernity and local values. This study aims to analyze the relationship between digital-era parenting, human resource quality (HRQ) as an intervening variable, and the balance between modernity and local values within the Baduy community. The research uses a qualitative approach with a case study method, involving 30 respondents from both Baduy Dalam and Baduy Luar. Data were collected through semi-structured interviews, participatory observations, and documentary studies. The findings reveal that parenting adaptive to technology has a significant impact on improving the quality of Generation Z's human resources. HRQ, in turn, plays a crucial role in bridging the gap between modernity and local values. In the Baduy Luar community, adaptive parenting allows Generation Z to utilize digital technology for productive activities, such as marketing handicrafts, without entirely abandoning cultural values. However, the risk of cultural degradation remains if parenting control over technology usage is not optimized. This study underscores that HRQ is a key factor in bridging tradition and modernity. The practical implications of this research include the need for digital literacy training oriented toward local values, for both parents and Generation Z. As a result, a sustainable balance between modernity and cultural preservation can be achieved.